Nanomaterials for sustainable tribology - Raina, Ankush (CRC Press, Taylor & Francis Group, 2023)
With the advent of nanotechnology, the properties offered by nano-sized particles in various engineering applications have revolutionized the area of material science. Furthermore, due to the use of nanomaterials in various engineering components, particularly in moving parts, it is imperative to understand the behavior of these nanomaterials under sliding conditions. Therefore, an augmented approach of nanotechnology and tribology has been addressed in this book. It presents recent advancements on the topics related to:- Mechanical and tribological behaviour of nanocomposites- Nanomaterials in lubricating oils- Synergetic effects of nanomaterials- Surface texturing at nano-scale- Nanocoatings for various applications- Biotribological applications of nanomaterialsNanomaterials for Sustainable Tribology covers major aspects of tribology of nanomaterials, and its current status and future directions. This book will provide the readers an insight on several aspects of tribology of nanomaterials. It will act as a strong stimulant for readers to appreciate and initiate further advancements in the field of tribology, particularly at nano-scale